2019
DOI: 10.3389/fnhum.2019.00440
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Racial Identity and Repetitive Head Impacts on Cognitive Function, Structural MRI-Derived Volumetric Measures, and Cerebrospinal Fluid Tau and Aβ

Abstract: Background: Factors of increased prevalence among individuals with Black racial identity (e.g., cardiovascular disease, CVD) may influence the association between exposure to repetitive head impacts (RHI) from American football and later-life neurological outcomes. Here, we tested the interaction between racial identity and RHI on neurobehavioral outcomes, brain volumetric measures, and cerebrospinal fluid (CSF) total tau (t-tau), phosphorylated tau (p-tau 181), and Aβ 1−42 in symptomatic former National Footb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 104 publications
(157 reference statements)
1
13
0
Order By: Relevance
“…Additionally, because black players are more likely to play high‐impact positions, presumed exposure may be driving the suggestion of CTE in clinical contexts. A recent study of symptomatic former professional football players has noted that black players had significantly higher indices of head injury, higher blood pressure, higher BMI, and lower right hippocampal volume than white participants . In our study, participants who played between 5 and 9 seasons showed a higher percentage of self‐reported CTE than those who played both fewer and more seasons.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Additionally, because black players are more likely to play high‐impact positions, presumed exposure may be driving the suggestion of CTE in clinical contexts. A recent study of symptomatic former professional football players has noted that black players had significantly higher indices of head injury, higher blood pressure, higher BMI, and lower right hippocampal volume than white participants . In our study, participants who played between 5 and 9 seasons showed a higher percentage of self‐reported CTE than those who played both fewer and more seasons.…”
Section: Discussionsupporting
confidence: 51%
“…A recent study of symptomatic former professional football players has noted that black players had significantly higher indices of head injury, higher blood pressure, higher BMI, and lower right hippocampal volume than white participants. 34 In our study, participants who played between 5 and 9 seasons showed a higher percentage of self-reported CTE than those who played both fewer and more seasons. Although we cannot say for certain why this is, it is possible that healthy worker bias may be at play where the most injured players aren't represented in populations of players with longer careers.…”
Section: Discussionmentioning
confidence: 43%
“…One limitation of this approach is that the NFL has not publicly released, nor have there been published reports of HIT System or other head impact sensor data from NFL players, thus resulting in the need to rely on college player HIT System data in these PEMs. We will combine the PEM with each participant’s football history (i.e., age of first exposure, level[s] and duration of play, position[s] played) to develop participant-specific estimates of cumulative exposure to head impacts [ 27 , 61 , 160 , 161 ]. Additional methods of estimating repetitive head impact exposure will be included as they become available.…”
Section: Methodsmentioning
confidence: 99%
“…For consistency, we automated the process using Multiple Artifact Rejection Algorithm 94,95 . Subsequent analyses were done in Fieldtrip 96 separately in the delta (1-5 Hz), theta (5)(6)(7)(8), alpha (8)(9)(10)(11)(12), beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and low gamma (30-80 Hz) bands [97][98][99] .…”
Section: Methodsmentioning
confidence: 99%
“…However, the data on cognitive outcomes long after mTBI (> 3 months) are mixed. For example, recent reviews reported no lasting cognitive deficits 18 20 , whereas athletes and veterans at > 1-year post-injury have lasting executive dysfunction 21 40 , and impaired working memory (WM) 41 , 42 . In these populations, effects may be heightened by blast injury 43 , and/or repeated head injury 44 .…”
Section: Introductionmentioning
confidence: 99%